IMPROVING THE COMMUNITY ECONOMY BASED ON ISLAMIC PHILANTHROPY IN SOCIAL AND RELIGIOUS INSTITUTIONS - Faridatun Najiyah, Noor Iffatin Nadhifah (STAI AL-HIDAYAT Lasem, 2023)
This study illustrates the importance of optimizing ZIS activities based on Islamic philanthropy from the perspective of religious morality. Zakat is not only considered as a religious ritual, but also as a moral obligation that goes beyond mere formal actions. LAZIZ demonstrates a commitment to managing ZIS funds professionally, with a focus on using funds for productive businesses aimed at improving community welfare. LAZIZ conducts a careful survey of mustahik to ensure that funds are distributed on target. In addition, LAZIZ applies a consumptive and productive approach in managing ZIS funds, by providing direct assistance and providing business capital through the BUM program.